The Impact of Content Marketing, Social Media Marketing and Online Convenience on Consumer Buying Decision Process - Omar Hamdan Mohammad Alkharabsheh; Bryan Ho Zhen (Universitas Internasional Batam, 2021)
With the rapid improvement of modern technology, the trend of how consumer purchase has been changed. Businesses are adopting digital marketing instead of conventional means of marketing. Products that were previously only sold in brick-and-mortar store are now selling online, such as apparel products. This research aims to identify the digital marketing elements that affect consumer buying decision process, namely content marketing (CM), social media marketing (SMM), and online convenience (OC). Self-administrative questionnaire was used to collect data from 236 respondents using Google Form. Descriptive and inferential analysis are conducted. Besides, the three elements of digital marketing (CM, SMM and OC) have significant impact on consumer buying decision process. This study provides evidence to business owner, marketers, and academician’s researchers that what are effectively affecting the consumer buying decision process in digital marketing in Malaysia so that they can allocate their marketing budget wisely.